«Per aspera ad astra». The way that leads us to teaching of Humanities - Olano García, Hernán Alejandro (Mercurio Peruano, 2020)
The present paper presents an exposition of humanistic studies as an essential requirement in university curricula. From their origins in medieval universities, and earlier in Greco-Latin academies, the humanities have served their purpose in the students overall education, whose goals should be, rather than scholarship or specialization, the development of an aesthetic and social sensibility, and the acquisition of intellectual habits such as the search for truth and the development of independent and rigorous thinking.